(untitled) (Research, Society and Development, 2021)
Human evolution has allowed strategies for partial and total edentulism to be developed and perfected. In this sense, contemporary implantology has allowed oral rehabilitation to be accessible to society, contributing to a better quality of life in the aesthetic, food and social spheres. Therefore, the general conditions of the patient are of paramount importance for the success of the processes for dental implants. Thus, the aim of this review was to relate several sources in search of information about the difficulties encountered in bone healing in patients with diabetes mellitus II who undergo bone implants. Searches were carried out on books, scientific articles and electronic journals. All works used as a research base report as a result several factors that influence the non-maintenance of homeostasis in the healing physiology of type II diabetes mellitus, and many implants may not achieve the desired success. The evaluated works report good experiences in the osseointegration process despite the organic difficulties caused by type II diabetes mellitus. However, it is evident the need to control this endocrinopathy so that the procedures achieve the desired healing.